The Extent Implementation of Managerial Decentralization in Jordan and its Impact on local development - et.al, Dr. Faraj Harahsheh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main purpose of this study is to analyze the extent implementation of managerial decentralization and its impact on local development in Jordan, the sample consists of (80) individuals with percentage (66.66%) (chairman of governorate council ,vice president of governorate council, member of the governorate council) in the north regions of Jordan, the results showed that the altitudes of the study sample towards independent variable (Managerial Decentralization) was positive with high degree except the variable (delegation of authority) which was of medium degree, and the altitudes of the study sample towards dependent variable (local development) was medium degree, also there is a significant statistical impact of Managerial decentralization (speed of achievement, simplification of procedures, delegation of authority, participation in decision-making) on local development in Jordan . The researchers recommended ( increasing interest in local development for regions and cities by increasing the budget allocated to governorates, improving services provided to citizens, paying attention to developing infrastructure, roads and transportation, taking care about improving health and educational services, reducing unemployment by providing jobs, reducing the community problems, listening to the problems of citizens and employees participation in delegation of authority.